Weegee’s City Secrets - Alan TRACHTENBERG (E-REA)
As a freelance photographer of crime, accidents, fires, and also of the recreational life of the city—scenes of violence and of pleasure—Weegee worked mainly at night and employed a powerful photoflash attachment to his press camera. His "secrets of shooting with photoflash" consist of practical technical advice for beginners. But within the rhetoric of his "secrets" there lie cogent and subtle reflections on the relation of light to darkness, especially on the way the flash of light makes darkness visible. In Weegee’s account, the photoflash gives photography the power of writing—writing with light, a mode of picturing uniquely suited to recording instants of life on city streets at night.